Cryptanalysis and design of signature schemes with identity ambiguity in the standard model - ZHANG Ming-wu1; YANG Bo1; YAO Jin-tao1; ZHANG Wen-zheng2 (Tongxin xuebao)
The security and flaw of the two anonymous signature schemes called ZLW（2008） and LHMM（2009） were analyzed,where the ZLW scheme couldn’t provide signed message verifiability and the LHMM scheme couldn’t resist on the multiple-known-signature existential forgery.A novel anonymous signature scheme was proposed that enforced the security level to Model3 security and reduced the computational cost,which only needed two multiple calculations in G in signing phase and n+1 bilinear pairing operators in verifying algorithm.